2017
DOI: 10.1038/srep41397
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of a cellulose synthase gene BoiCesA affects the leaf anatomy, cellulose content and salt tolerance in broccoli

Abstract: Cellulose is the major component of cell wall materials. A 300 bp specific fragment from the cDNA fragment was chosen to insert into vector pFGC1008 at forward and reverse orientations to construct the recombinant RNAi vector. Knockdown of BoiCesA caused “dwarf” phenotype with smaller leaves and a loss of the content of cellulose. Moreover, RT-PCR analysis confirmed that the expression of the RNAi apparatus could repress expression of the CesA gene. Meanwhile, examination of the leaves from the T3 of RNAi tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Cellulose synthase ( CESA ) genes play roles in the synthesis of primary and secondary cell wall (Zhang et al , 2016). Secondary walls have a large impact on plant adaptation to the environment, and some CESA genes and cellulose synthase-like genes ( CSL ) are involved in salt tolerance (Zhu et al , 2010 a ; Zhu et al , 2010 b ; Wang et al ., 2016; Zhang et al , 2016; Li et al , 2017; Zhang et al , 2018). Our RNA-Seq data indicated that there were 31 cellulose synthase family genes down-regulated by AtHSFA7b (see Supplementary Table S5), indicating that they might be involved in AtHSFA7b-mediated salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Cellulose synthase ( CESA ) genes play roles in the synthesis of primary and secondary cell wall (Zhang et al , 2016). Secondary walls have a large impact on plant adaptation to the environment, and some CESA genes and cellulose synthase-like genes ( CSL ) are involved in salt tolerance (Zhu et al , 2010 a ; Zhu et al , 2010 b ; Wang et al ., 2016; Zhang et al , 2016; Li et al , 2017; Zhang et al , 2018). Our RNA-Seq data indicated that there were 31 cellulose synthase family genes down-regulated by AtHSFA7b (see Supplementary Table S5), indicating that they might be involved in AtHSFA7b-mediated salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Among the identified proteins in broccoli, cell wall cellulose protein was found. It has been suggested that the regulation of cell wall cellulose synthesis has an important role in polysaccharide metabolism and adaptations of broccoli plants to salt stress [ 52 ]. Knockdown mutants for the cellulose synthase gene showed overexpressed BoPIP2;2 and BoPIP2;3 aquaporins compared to the WT plants, pointing out that these two isoforms enhanced the salt tolerance of mutant plants.…”
Section: Discussionmentioning
confidence: 99%
“…8 by functional nominations. Similar functional genes have been reported controlling salt tolerance or abiotic stress in plants, such as Callose synthase which plays an important role in response to multiple biotic and abiotic stresses, including salt stress [57, 58]. In addition, V-type H + -transporting ATPase subunit expressed in the roots, energizes sodium sequestration into the central vacuole and enhances salt tolerance in plants [5961].…”
Section: Discussionmentioning
confidence: 74%